Analysis of occupational safety and health at chemical manufacturer with HIRARC method - Sahara, Adinda Suchieyati; Herwanto, Dene; Nugraha, Billy (Universitas Sultan Ageng Tirtayasa, 2023)
PT Timuraya Tunggal is a leading supplier and manufacturer of chemical products. Within its operations, potential hazards exist, notably in the sulfuric acid production section, necessitating the role of occupational safety and health to prevent and mitigate accidents. This research adopts a qualitative descriptive approach, utilizing both primary and secondary data sources. The collected data undergoes processing using the HIRARC method, identifying hazards primarily through direct observation in the burner process. The results and discussions of this study conclude the identification of two potential hazards in the burner process at PT Timuraya Tunggal, comprising one low-risk, two moderate-risk, and one high-risk hazard. Control recommendations proposed for the burner process include administrative controls such as avoiding the burner area unnecessarily, installing guardrails, mandating the use of respirator masks and scrubbers, and implementing the use of caustic soda for SO2 neutralization. Additionally, a suggested control for the burner process involves prominently displaying warning signs indicating 'hot surfaces, do not touch.